2006
DOI: 10.1007/s00441-005-0135-7
|View full text |Cite
|
Sign up to set email alerts
|

Endothelia of term human placentae display diminished expression of tight junction proteins during preeclampsia

Abstract: This study explores the molecular composition of the tight junction (TJ) in human term placenta from normal women and from patients with preeclampsia, a hypertensive disorder of pregnancy. Maternal endothelial dysfunction is a critical characteristic of preeclampsia; hence, we have analyzed its impact on placental vessels. The study concentrates on the TJ because this structure regulates the sealing of the paracellular route. We have found that, in placental endothelial vessels, TJ components include the perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 71 publications
2
23
0
Order By: Relevance
“…Claudins are tight junctional molecules, which are present in epithelial, endothelial and mesothelial cells (21,23,43). Claudin 1 and 4 are commonly found in epithelial cells and claudins 1, 3 and 5 have been detected in endothelial cells of term placenta (44). However, in that paper, the expression of claudin was not evaluated in the earlier trimesters.…”
Section: Discussionmentioning
confidence: 91%
“…Claudins are tight junctional molecules, which are present in epithelial, endothelial and mesothelial cells (21,23,43). Claudin 1 and 4 are commonly found in epithelial cells and claudins 1, 3 and 5 have been detected in endothelial cells of term placenta (44). However, in that paper, the expression of claudin was not evaluated in the earlier trimesters.…”
Section: Discussionmentioning
confidence: 91%
“…Claudins are essential components of the intercellular tight junction (TJ). Endothelia of the terminal villi display diminished expression of TJ proteins in case of PE (Liévano et al, 2006) and, accordingly, the effect of PE upon endothelial TJ proteins is a significant decreased expression of claudins (Leach et al, 2000(Leach et al, , 2002. This diminished expression might generate TJs that allow a less restrictive passage of molecules through the paracellular pathway and might arise in the placenta as a consequence of hypertension experienced by the preeclamptic mother in whom an increase in interstitial fluid is thought to be attributable to the capillary leakage of fluid and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…One study in mice has shown that the increase in the expression of the glycosaminoglycan hyaluron which is associated with cervical prelabour ripening not only occurs in the cervical stroma but also, to a lesser extent, in the epithelium[15]. Studies of human and animal epithelial tissue have highlighted the physiological role of gap junctional proteins such as occludin and the claudins in modulating cell contact and permeability [16-19]. Little is known of the epithelial changes associated with human cervical preparation for birth and changes in these gap junctional proteins have not been described in the cervix during human pregnancy.…”
Section: Discussionmentioning
confidence: 99%